Deep cytogenetics analysis reveals meiotic recombination depletion in species of Senecio (Asteraceae) - Lopez, Marina G. (2013)
Background: Senecio is the largest genus in the Asteraceae family growing in all environments around the world. It displays taxonomic and systematical difficulties. Cytogenetic knowledge of this genus is ancient, scarce and mainly restricted to chromosome number records. Results: In this study we analyzed chromosome number, meiotic configuration, bivalent morphology, meiotic behavior and pollen grain stainability on 100 accessions of 27 different polyploid Senecio L. sect Senecio entities. Median, standard deviation and mode were calculated for number and position of chiasmata and meiotic recombination was statistically evaluated. Although high frequency of multivalents and associated meiotic irregularities are expected in high polyploids, bivalents predominance and, consequently, regular meiosis were observed, with normal sporogenesis and high pollen grain stainability. Conclusion: Depletion in the total chiasmata was significant only in some species but the terminal position was preferential in all the entities analyzed, indicating significant reduction in recombination. The regular meiosis observed suggest that intra and intergenomic reorganization process occur quickly and efficiently in this genus. Mechanisms of diploidization, common to all polyploids, are reinforced by the strong reduction in crossing-over rushing polyploids stabilization.